Distributions of waterborne pathogens in raw wastewater based on a 14-month, multi-site monitoring campaign. (15th April 2022) - Pecson, Brian M.; Darby, Emily; Danielson, Richard; Dearborn, Yeggie; Giovanni, George Di; Jakubowski, Walter; Leddy, Menu; Lukasik, George; Mull, Bonnie; Nelson, Kara L.; Olivieri, Adam; Rock, Channah; et al.
Highlights: Pathogen concentration data are critical for setting reuse treatment requirements. 120 raw wastewater samples were collected over a 14-month monitoring period. Results provide industry with extensive dataset to use for regulatory development. Optimized methods provide high sensitivity, accuracy, and reproducibility. Abstract: The California State Water Resources Control Board is the first regulatory body in the United States to develop statewide regulations for direct potable reuse (DPR). To support this effort, a pathogen monitoring campaign was undertaken to develop and implement an optimized standard operating protocol to better characterize the concentration of human pathogens in raw wastewater. Methods to detect relevant viral and protozoan pathogens in raw wastewater were optimized and implemented during a 14-month monitoring campaign. Over 120 samples were collected from five wastewater treatment plants treating a quarter of California's population. Samples were analyzed for two protozoa ( Cryptosporidium and Giardia ) using microscopy methods, three enteric viruses (enterovirus, adenovirus, and norovirus) using culture and/or molecular methods, and male-specific coliphage using culture methods. The method recovery efficiency was measured in every protozoa sample and every other virus sample to confirm minimum recovery efficiencies were achieved and to correct the concentrations for pathogen losses during sample processing. The results from this study provide the industry with a large, high-quality dataset as demonstrated by the high degree of method sensitivity, method recovery, and QA/QC steps. Such high-quality data on pathogen concentrations in raw wastewater are critical for confirming the level of treatment needed to reduce pathogen concentrations down to acceptable levels for potable water in DPR projects. Graphical abstract: Image, graphical abstract